Measurement while drilling (MWD) : signal analysis, optimization, and design - Chin, Wilson C. (Hoboken, New Jersey : Scrivener Publishing/Wiley, 2014)
Trade magazines and review articles describe MWD in casual terms, e.g., positive versus negative pulsers, continuous wave systems, drilling channel noise and attenuation, in very simple terms absent of technical rigor. However, few truly scientific discussions are available on existing methods, let alone the advances necessary for high-data-rate telemetry. Without a strong foundation building on solid acoustic principles, rigorous mathematics, and of course, fast, inexpensive and efficient testing of mechanical designs, low data rates will impose unacceptable quality issues to real-time f.
4 Transient Constant Area Surface and Downhole Wave Models; 4.1 Method 4-1. Upgoing wave reflection at solid boundary, single transducer deconvolution using delay equation, no mud pump noise; 4.1.1 Physical problem; 4.1.2 Theory; 4.1.3 Run 1. Wide signal -- low data rate; 4.1.4 Run 2. Narrow pulse width -- high data rate; 4.1.5 Run 3. Phase-shift keying or PSK; 4.1.6 Runs 4,and 5. Phase-shift keying or PSK, very high data rate; 4.2 Method 4-2. Upgoing wave reflection at solid boundary, single transducer deconvolution using delay equation, with mud pump noise; 4.2.1 Physical Problem.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Oil well logging, Electric; Oil well drilling; Orientation -- Measurement; Wells -- Fluid dynamics; Flow meters; Formation damage (Petroleum engineering) -- Measurement -- Congresses; Geophysical well logging; Oil well logging -- Congresses; Petroleum -- Geology -- Congresses; TECHNOLOGY & ENGINEERING -- Mining; Electronic books; Electronic books